1980
DOI: 10.1121/1.384769
|View full text |Cite
|
Sign up to set email alerts
|

Representative hearing levels by race and sex in North Carolina industry

Abstract: An extensive sample of North Carolina industrial audiometric test data has been compiled. The sample includes data from several different types of industrial environments, with the size of the industries represented ranging from less than fifty to over eight thousand employees. The total population considered is in excess of 14000 employees. The data are examined using analytical techniques developed over the past six years while investigating the effectiveness of industrial hearing conservation programs. One … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
3

Year Published

1982
1982
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 0 publications
0
25
0
3
Order By: Relevance
“…Previous reports of racial differences for behavioral thresholds have been described for those with hearing loss due to noise exposure, or those older than 30 years. In general, among noiseexposed workers, Caucasians have been shown to have poorer behavioral thresholds than African Americans (Henselman et al, 1995;Ishii & Talbott, 1998;Karsai et al, 1972;Royster et al, 1980b). For non-noise-exposed people over 30 years of age, differences varied depending on the report, but generally Caucasian males have been shown to have more hearing impairment than African-American males for conventional frequencies greater than 2000 Hz (Bunch & Raiford, 1931;Post, 1964;Roberts & Bayliss, 1967).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous reports of racial differences for behavioral thresholds have been described for those with hearing loss due to noise exposure, or those older than 30 years. In general, among noiseexposed workers, Caucasians have been shown to have poorer behavioral thresholds than African Americans (Henselman et al, 1995;Ishii & Talbott, 1998;Karsai et al, 1972;Royster et al, 1980b). For non-noise-exposed people over 30 years of age, differences varied depending on the report, but generally Caucasian males have been shown to have more hearing impairment than African-American males for conventional frequencies greater than 2000 Hz (Bunch & Raiford, 1931;Post, 1964;Roberts & Bayliss, 1967).…”
Section: Discussionmentioning
confidence: 95%
“…The effects of race on behavioral thresholds have also been studied in occupations known to cause hearing loss. These studies, although the amount and level of exposure varied, generally have shown that Caucasians have poorer behavioral thresholds than African Americans (Henselman et al, 1995;Ishii & Talbott, 1998;Karsai et al, 1972;Royster et al, 1980b). Regarding gender influences, some studies have shown that females generally have more sensitive hearing than males (Hallmo et al, 1994;Lö ppö nen et al, 1991;Stelmachowicz et al, 1989) , while others have shown no gender differences (Betke, 1991;Dunckley & Dreisbach, 2004;Frank, 1990;Osterhammel & Osterhammel, 1979).…”
Section: Sumariomentioning
confidence: 93%
“…Like the crossing defect, it reflects miswired neuronal connections probably established in the embryo (Pak et al, 1987;Shatz & Kliot, 1982;Winterson & Collewijn, 1981). Two other melanin effects are apparent only in the adult: melanin levels in the eye affect visual thresholds-hypopigmented animals have impaired night vision (Balkema, 1988;Drager & Balkema, 1987;Balkema et al, 1981), and melanin levels in the inner ear influence auditory adaptation and, on the long term, chronic noise trauma -darkly pigmented populations have slightly better hearing than lightly pigmented populations (Hood et al, 1976;Royster et al, 1980;Tota & Bocci, 1967). The effects on visual thresholds, and probably also on auditory adaptation, are "functional": they are not due to abnormal neuronal connections, but they seem to reflect the acute influence which the pigmented nutrient layers -the retinal pigment epithelium and choroid in the eye, and the stria vascularis in the ear -exert over sensory-receptor function (Drager & Balkema, 1987;Balkema et al, 1983).…”
Section: Discussionmentioning
confidence: 96%
“…During localization tasks, males tend to discriminate between small differences in interaural time and level differences more accurately and consistently than females (Langford, 1994). However, males incur greater permanent noise-induced hearing loss (Royster et al, 1980). Using a toneidentification paradigm, Sagi et al (2007) report gender differences in the psychophysical parameter, n, found in Stevens' power law, L = ku n , relating the loudness of a tone, L, to the physical intensity of the tone, u.…”
Section: Introductionmentioning
confidence: 98%